TRANS7 EDITORIAL MISINTERPRETATION IN THE UNCENSORED XPOSE PROGRAM REGARDING THE TRADITIONS OF ISLAMIC BOARDING SCHOOL SYMBOLIC INTERACTION THEORY STUDY - Saiful Romadon; Ade Budi Santoso; Jatayu Hadi Prakoso; Irwansyah Nuzar (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study discusses the Trans7 editorial team's misinterpretation of Islamic boarding school traditions in the Xpose Uncensored program: A study of symbolic interaction theory. The research used a qualitative method with a case study approach. The results show that every place, group, institution, organization, and the like has traditions and symbols whose meanings cannot be generalized. Islamic boarding schools are one of the oldest educational institutions in Indonesia, possessing their own unique characteristics and diverse traditions in their learning process.